Emergence of coronavirus disease 2019 (COVID-19) in Austria - Kreidl, Peter (Wien Klin Wochenschr, 2020)
This is a report on the first identified cases of coronavirus disease 2019 (COVID-19) in Austria. The first documented case was a person who stayed in Kühtai, Tyrol, from 24 to 26 January 2020, and had been infected by a Chinese instructor in Starnberg (Germany) between 20 and 22 January. This counts as a German case since her diagnosis was eventually made in Munich (Germany) on 28 January. On 25 February, two cases imported from Italy were diagnosed in Innsbruck but again no secondary cases were identified in Austria. The first three infections of Austrian inhabitants were detected on 27 February in Vienna. The two resulting clusters finally included 6 (source of initial infection unknown) and 61 cases. Most likely, Italy was the source of the latter cluster. On 12 March the first fatal case of COVID-19 in Austria was reported, a 69-year-old Viennese who died in a Vienna hospital after returning from a cruise ship tour in Italy. On 6 March three autochthonously acquired cases were reported in the Tyrol, all related to the ski resort Ischgl. Of the first 14 Islandic COVID-19 cases infected in Ischgl, 11 had already returned to Iceland on 29 February. We consider that the incriminated barkeeper, who tested PCR positive on 7 March, was neither the primary case nor a superspreader. In our opinion, undetected transmission of SARS-CoV‑2 had been ongoing in Ischgl prior to the first laboratory confirmed cases. Our data also underline that the introduction of SARS-CoV‑2 into Austria was not one single event.